Evaluation the Antibacterial Effect of Rosemary and Lemon Grass Essential Oils against Planktonic and Biofilm of MRSA - Zainab Zamel Khalaf (Journal of Global Pharma Technology, 2020)
There has been increasing interest in volatile oils in recent years due to the need for new treatments against microbes. Bacterial resistance is widespread worldwide and the first cause of this resistance is the excessive use of antibiotics and bad practices to combat infection in hospitals, making it one of the biggest issues at present. In this study, twenty bacterial isolates of methicillin-resistant Staphylococcus bacteria were diagnosed and all were diagnosed using Vitek. The synergistic effect of the rosemary and lemongrass essential oil against these bacteria was studied in the form of suspended or single cells and when they formed the biofilm. Different concentrations of both essential oils were used to experiment the minimal inhibitory (MIC) effect on these bacteria. The effect of each oil was studied separately and then their synergistic effect was investigated. The bacteria's ability to produce the biofilm using the Tissue culture plate method Whether it was strong, moderate, or weak, and then investigated the inhibitory properties of each oil against the biofilm of the bacteria and also studied the synergistic effect of both oil against the biofilm of the bacteria. The findings proposed that all isolates were affected and inhibited with lemon grass essential oil except for one isolate and was an oil effect Lemon grass is larger compared to rosemary essential oil, but the synergistic effect was better in compare with the effect of each oil alone. The results of the biochemistry of the bacteria showed that 15 isolates of Staphylococcus aureus were formed of a strong biofilm and 4 isolates formed for a medium biofilm and one isolate only for a weak. The results also find that the lemon grass and rosemary essential oil had an effect against the biofilm but with different concentrations. There were 3 isolates that were not affected by each one of plant oil (3, 6 and 10). The synergistic effect of both essential oils showed that all isolates were inhibited except (6, 9 and 10). Keywords: Essential oils; Synergistic effect; MRSA; Antibacterial activity, Biofilm.